Navigating cultural connotations in translation: blending paradigms to illuminate Diǎngù and Shúyǔ in Chinese Premier Li Keqiang's government reports - Sun, Aina; Subramaniam, Vijayaletchumy A. P. (Academy Publication, 2024)
This study delves into the translation challenges of Premier Li Keqiang's Report on the Work of the Government (RWG), a notable piece in Chinese political discourse. It focuses on translating the cultural nuances embedded in Diǎngù (allusions) and Shúyǔ (formulaic expressions) into English to enhance global comprehension. Using an interpretive qualitative methodology, the research identifies deficiencies in translating these cultural connotations from the RWG (2013-2022) and explores their root causes, considering translation strategies employed. It integrates Venuti's theories of domestication and foreignization with Aristotle’s concepts of logos and clarity in style. Thematic analysis uncovers key translation issues: loss of original imagery, disrupted logical flow, and verbose redundancy, primarily due to challenges in maintaining logos and stylistic clarity. The study's significance lies in pinpointing these translational gaps and introducing a novel approach that amalgamates diverse theoretical frameworks, offering unique insights and methods to effectively connect language, culture, and political communication in translation studies.